A Speech Act Analysis of a Pre-Service Teacher in an EFL Classroom - Halimatuz Zahra; Widya Caterine Perdhani; Didik Hartono (Institut Agama Islam Negeri Palopo, 2022)
This research aims to find out and analyze the classification of speech acts and the function performed by a pre-service English teacher at SMAN 7 Malang. This implies a qualitative descriptive study, looking at the pre-service English teacher’s talk in an EFL classroom. The present study focuses on the classification of speech acts employed by Searle. The finding of this study indicates four speech act types uttered by the teacher. It consists of 41 representatives out of 185 utterances, 120 utterances of directive type, 7 utterances of commissives, and 17 utterances of expressive. To conclude, the results of this study show that directive type dominates the data with 64.9% out of the utterances, followed by representatives at 22.2%, expressive at 9.2%, and commissives at 3.8%.